Alcohol Dehydrogenases and Acetaldehyde Dehydrogenases are Beneficial for Decidual Stromal Cells to Resist the Damage from Alcohol. (5th October 2016) - Li, Zi-Long; Li, Meng-Qi; Li, Shu-Yun; Fu, Yong-Sheng; Yang, Zeng-Ming
Abstract: Aims: The aim of this study was to examine the effect of alcohol on the decidualization of human endometrial stromal cells during early pregnancy. Methods: During in vitro decidualization, human endometrial stromal cells were treated with alcohol, 4-methylpyrazole hydrochloride (FPZ), the inhibitor of alcohol dehydrogenases (ADHs), and tetraethylthiuram disulfide (DSF), the inhibitor of acetaldehyde dehydrogenases (ALDHs), respectively. Cell viability and decidualization were examined. Apoptosis and proliferation were also evaluated. Results: The findings showed that ADHs and ALDHs were up-regulated during decidualization. After alcohol treatment, the cell viability of decidual stromal cells was significantly higher than control, which was abrogated by FPZ or DSF. When cells were treated with alcohol, proliferation-related signal pathways were up-regulated in decidualized cells. Additionally, FOXO1 transcriptionally up-regulates ADH1B. Conclusion: Our study provided an evidence that highly expressed ADHs and ALDHs endow decidual stromal cells an ability to alleviate the harm from alcohol.